Social and Cultural Imaginaries of Cattle Ranchers in a Territory in Conflict - Bastidas Artunduaga, Nicolas Faubricio; Amaya Castaño, Gloria Clemencia; Sánchez Castillo, Verenice (Sociedad y Economía, 2024)
Extensive cattle ranching in Caquetá is the economic activity that contributes most to the department’s GDP. However, it is also the productive system to which most environmental problems are attributed. The cattle ranchers participating in the study have been interested in moving towards the implementation of Silvopastoral Systems (SSP) but have encountered several barriers and limitations to their adoption. The objective of the manuscript is to analyze the sociocultural imaginaries concerning the adoption of SSP. The study was qualitative; in-depth interviews were conducted, and the data were processed using Greimasian semiotics and the qualitative data processing software ATLAS.ti 23. The main findings indicate that the intermittency of the intervention processes, the lack of sufficient capital, and the scourge of conflict have been determining factors in the non-adoption of SSPs.